Evaluation of an online-based self-help program for patients with generalized anxiety disorder: a randomized controlled trial - Rubel, Julian; Väth, Teresa; Hanraths, Sofie; Prüßner, Luise; Timm, Christina; Hartmann, Steffen; Barnow, Sven; Lalk, Christopher (Internet interventions, 2024)
Objectives - This study aimed to evaluate the effects of an online self-help intervention for generalized anxiety disorder (GAD). Our primary outcomes were generalized anxiety symptoms, measured using the Generalized Anxiety Disorder - 7 (GAD-7; Spitzer et al., 2006), and wellbeing based on the World Health Organization Wellbeing Index - 5 (WHO-5; Topp et al., 2015). - Methods - A total of 156 German-speaking patients aged 18 to 65 with a diagnosis of GAD and internet access were included in this randomized controlled trial. The intervention group (N = 78) received access to a 12-week online self-help program, while the waitlist control group (N = 78) received access after the 12-week waiting period. - Results - The intervention group showed a significant improvement in generalized anxiety symptoms compared to the control group (t(df = 123.73) = 4.52, p < .001) with a large effect size (d = 0.88, 95 %-CI: 0.50; 1.26). Additionally, the intervention group demonstrated a significant increase in wellbeing compared to the control group (t(df = 87,86) = 3.48, p < .001), with a moderate effect size (d = 0.62, 95 % CI: 0.27; 0.98). However, no significant effects were observed for secondary outcomes of functional impairments, work productivity, mental health literacy, and healthcare demands. For exploratory outcomes, improvement was found for anxiety and worry symptoms. - Conclusions - These findings suggest that an online-based self-help intervention effectively reduces GAD symptoms and improves overall wellbeing. Future research should explore the long-term effects of this intervention and investigate potential mechanisms underlying its efficacy. - Public health implications - Online-based self-help programs provide a promising treatment option for individuals with GAD who face barriers to traditional face-to-face therapy.
Online verfügbar: 23. Januar 2024, Artikelversion: 1. Februar 2024
Gesehen am 08.04.2024